Phosphate modification of calcium aluminate cement to enhance stability for immobilisation of metallic wastes. (November 2014) - Chavda, M. A.; Kinoshita, H.; Provis, J. L.
<x content-type="archive" xml:space="preserve">Abstract</x> Cementing systems based on calcium aluminate cement (CAC) have been studied as an alternative cement matrix for the encapsulation of intermediate level wastes (ILWs) arising from the nuclear industry. Calcium aluminate cement based systems have great potential for the incorporation of aluminium containing ILW owing to the near neutral internal pH of these binders. However, CAC based binders usually undergo phase conversion from the metastable hydration phases C3AH6 and/or C2AH8 to the stable C3AH6, resulting in strength regression and dimensional instability. The present study investigates the feasibility of CAC modification to prevent this detrimental process of phase conversion. Two different types of sodium phosphates are used to modify a CAC system, and the setting behaviour and the mineralogy of the binder products were studied. It is shown that it is possible to avoid the conventional phase conversion of CAC hydrates due to the formation of an amorphous aluminate phase in place of the metastable hydrates, leading to the production of a phase assemblage, which is stable for at least 180 days.